PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) BERBANTUAN KOMIK BERGAMBAR UNTUK MENINGKATKAN MINAT MEMBACA DAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SDN 10 TIGA DESA - Emiliana; Margaretha Lidya Sumarni (STKIP Subang, 2026)
This study was motivated by the low reading interest and Indonesian language learning outcomes of fifth-grade students at SDN 10 Tiga Desa. The purpose of this study was to improve students’ reading interest and learning outcomes through the implementation of the Think Pair Share (TPS) cooperative learning model assisted by illustrated comics. This study employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were 23 fifth-grade students of SDN 10 Tiga Desa. Data were collected through observation, questionnaires, tests, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The results indicated that the implementation of the Think Pair Share (TPS) model assisted by illustrated comics effectively improved students’ reading interest and learning outcomes. Reading interest mastery increased from 26.08% in the pre-cycle to 43.48% in Cycle I and 95.65% in Cycle II. The average reading interest score also improved from 66.48 to 76.65 and 78.26. Meanwhile, learning outcome mastery increased from 56.52% in the pre-cycle to 78.26% in Cycle I and 86.95% in Cycle II. These findings demonstrate that the Think Pair Share (TPS) cooperative learning model assisted by illustrated comics can create an active and enjoyable learning environment, thereby improving students’ reading interest and Indonesian language learning outcomes.